A New Family of 3d–4f Bis‐Calix[4]arene‐Supported Clusters. Issue 56 (7th September 2017) - Coletta, Marco; McLellan, Ross; Sanz, Sergio; Gagnon, Kevin J.; Teat, Simon J.; Brechin, Euan K.; Dalgarno, Scott J.
Abstract: Calix[4]arenes are versatile ligands that, whilst also serving other purposes, can act as platforms for the synthesis of a wide range of 3 d, 4 f, and 3 d –4 f polymetallic clusters. The empirical metal ion binding rules established for calix[4]arene are closely mirrored by bis‐calix[4]arene, a relatively new ligand in which two equivalents of the former are directly tethered at a methylene bridge position. The direct tethering within bis‐calix[4]arene gives rise to some structural features that are related to calix[4]arene coordination chemistry, but the prevailing clusters have fascinating new topologies and coordination behaviors. Here, we present the synthesis of a family of new bis‐calix[4]arene‐supported 3 d –4 f clusters, as well as their structural characterization and magnetic properties. Comparison is drawn with calix[4]arene coordination chemistry, showing logical extension of common structural fragments and cluster capping behaviors upon moving to bis‐calix[4]arene. This approach therefore holds great potential for tuning cluster formation and composition at a high level through subsequent ligand alteration. Abstract : Bis‐calix[4]arene is a versatile ligand that has been used to form a new family of 3 d –4 f polymetallic clusters. Empirical metal ion binding rules established for calix[4]arene are closely mirrored in this ligand, suggesting that one may use coordination preferences and ligand alteration/design in order to tune both cluster formation and composition at a high level in complex multi‐component systems.